Pengaruh Food Vloggers pada Niat Beli di Media Sosial - Erry Donneli (Yayasan Literasi Sains Indonesia, 2023)
The purpose of this study is to determine the relationship between the influence of food vloggers on purchase intention on social media (Youtube and Instagram) which is measured using indicators, namely: credibility, para-social interaction (psi), homophilic attitude, physical attractiveness, social attractiveness, entertainment motives, relationship building motives and time spent on social media. Purchase intention variable as the dependent variable. This study used 200 audience respondents who had visited and watched reviews of food vloggers on social media (youtube and instagram). The results of hypothesis testing as a whole, the simultaneous test proves that the credibility hypothesis and parasocial interactions have a significant effect on purchase intention with a significance of 0.00 <0.05. In addition, based on the independent t-test, it can be seen that Food Vloggers have a positive influence on Purchase Intention on social media (YouTube and Instagram) with a significance level of 0.00 <0.05. In testing the coefficient of determination, it is known that the influence of food vloggers with indicators of credibility and PSI on purchase intention has an effect of 51.1%, which means that the level of variables outside this study has a lower effect on customer satisfaction.